2021
DOI: 10.3390/ma14226787
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Finishing on the Pilling Resistance of Linen/Silk Woven Fabrics

Abstract: The pilling resistance of fashion fabrics is a fundamentally important and frequently occurring problem during cloth wearing. The aim of this investigation was to evaluate the pilling performance of linen/silk woven fabrics with different mechanical and chemical finishing, establishing the influence of the raw material and the peculiarities of dyeing and digital printing with different dyestuff. The pilling results of the dyed fabrics were better than those of the grey fabrics and even a small amount of synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Eventually, the fibers that bind the pills to the surface break down and a hole or thinning occurs [ 4 , 15 ]. The abrasion resistance and propensity to surface pilling of sock knits are influenced by many factors, such as the type of fibers and blends, the structure of the yarns, the construction of the knit and the finish [ 4 , 17 , 39 ]. Various researchers have studied the abrasion resistance and surface pilling tendency [ 3 , 4 , 15 , 20 , 29 , 33 ] of sock knits.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, the fibers that bind the pills to the surface break down and a hole or thinning occurs [ 4 , 15 ]. The abrasion resistance and propensity to surface pilling of sock knits are influenced by many factors, such as the type of fibers and blends, the structure of the yarns, the construction of the knit and the finish [ 4 , 17 , 39 ]. Various researchers have studied the abrasion resistance and surface pilling tendency [ 3 , 4 , 15 , 20 , 29 , 33 ] of sock knits.…”
Section: Introductionmentioning
confidence: 99%
“…For example, treatments such as singeing and biopolishing are sometimes used remove protruding fibre ends thereby reducing hairiness and improving pilling performance. (Ciechañska and Nousiainen, 2005;Tomaney, 2015;Hossain et al, 2021;Kumpikaitė et al, 2021). agitation encountered in regular use leads to their formation.…”
Section: Fabric Constructionmentioning
confidence: 99%
“…Various previous researchers found that heat setting, singeing, and cropping can improve the pilling performance for polyester/wool blends [1]. A linen/silk blend study found that the printed fabric showed better pilling performance for both with and without singeing [2]. In the case of the viscose/polyester blend, the pilling phenomenon after garment dyeing was better [3].…”
Section: Introductionmentioning
confidence: 99%